Existing Performance of Cocoa Agroindustry: Learn From Pt. Indonesia Hijau, Polewali Mandar, Indonesia - Natasya Kautsar Muthia; Arsyad Muhammad; Nixia Tenriawaru A. (BIO Web of Conferences, 2024)
PT. Indonesia Hijau carries out innovation in the form of a processing business made from fermented cocoa beans. Processing cocoa beans into several types of chocolate products creates added value and also sells buy order chocolate products. This research aims to analyze production performance and marketing mapping of processed chocolate products. The method used in this research is quantitative descriptive analysis. The results of the production performance of PT. Green Indonesia from the productivity aspect is categorized as good (>21,55 kg/HOK) and the capacity aspect is also categorized as good (>0.7). From the aspect of raw material and product quality, PT Indonesia Hijau has SNI, P-IRT, Halal and BPOM status. Apart from that, the flexibility aspect is considered to be good because it meets 3 dimensional measurements and also has a relatively good process speed aspect. However, this research suggests that the use of e-commerce in marketing can be optimized. Apart from that, you need to think about product delivery, which currently still takes a long time (because you have to transit first) in several cities, before arriving at the final destination city by means of the local government making a port of delivery of goods.